Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1165/rcmb.2010-0231oc
|View full text |Cite
|
Sign up to set email alerts
|

Receptor for Advanced Glycation End-Products Signals through Ras during Tobacco Smoke–Induced Pulmonary Inflammation

Abstract: We previously demonstrated up-regulation of the receptor for advanced glycation end-products (RAGE) and its ligands by cigarette smoke extract (CSE) in rat R3/1 cells, a type I-like alveolar epithelial cell line. However, RAGE-mediated intracellular signaling pathways that lead to pulmonary inflammation remained unclear. Using ELISAs, we demonstrate that alveolar epithelial cell lines exposed to 25% CSE for 2 hours induce the activation of Ras, a small GTPase that functions as a molecular switch in the control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 53 publications
1
51
0
Order By: Relevance
“…Ras is a molecular switch already implicated in smoke-induced lung inflammation mediated by RAGE (27). Lungs from SHSexposed wild-type mice presented significantly increased levels of active Ras compared with room air controls (Fig.…”
Section: Rage Mediates the Activation Of Shs-induced Ras And Nf-bmentioning
confidence: 94%
See 1 more Smart Citation
“…Ras is a molecular switch already implicated in smoke-induced lung inflammation mediated by RAGE (27). Lungs from SHSexposed wild-type mice presented significantly increased levels of active Ras compared with room air controls (Fig.…”
Section: Rage Mediates the Activation Of Shs-induced Ras And Nf-bmentioning
confidence: 94%
“…Of interest to the current investigation, RAGE expression is prominently detected in the alveolar compartments of smokers with COPD (48). Additionally, studies have revealed inflammatory abrogation after siRNA knockdown of RAGE in human lung cells (27) and impaired smoke-induced lung inflammation mediated by primary pulmonary macrophages isolated from RAGE knockout mice (32). Due to its importance in diverse inflammatory conditions, RAGE abrogation has been suggested as a possible therapeutic intervention for COPD (5).…”
mentioning
confidence: 95%
“…To obtain BALF, mice were sedated and then exsanguinated to ensure euthanasia as outlined previously (39). BALF was specifically harvested through the instillation and recovery of 7 1-ml boluses of PBS attached to a catheter for a total of 7 ml.…”
Section: Methodsmentioning
confidence: 99%
“…The receptor for advanced glycation endproducts (RAGE) is a member of the immunoglobin superfamily of cell surface receptors found in various cell types including smooth muscle cells, fibroblasts, macrophages, and epithelium (39). RAGE is most abundant in the lung (2) with sparse expression by alveolar type (AT) II cells and abundant expression on membranes of differentiated ATI cells (43).…”
mentioning
confidence: 99%
“…They induce DNA adducts, mainly 6-methyl-guanine, interfere with DNA replication and can damage proliferating cells, including those of the immune system compartment [15]. Smoke derivatives induce upregulation of antiapoptotic factors and activation of the transcription factor NF-κB, whose function is associated with autoimmune and neoplastic processes [16]. Moreover, tobacco smoke induces reactive oxygen species (ROS) which activate the expression of proinflammatory genes, such as interleukin-8 and TNFα and promote chronic inflammation [17].…”
Section: Tobacco Smoke Alcohol Consumption and Head And Neck Cancersmentioning
confidence: 99%